2004
DOI: 10.1073/pnas.0307101101
|View full text |Cite
|
Sign up to set email alerts
|

New biphenol-based, fine-tunable monodentate phosphoramidite ligands for catalytic asymmetric transformations

Abstract: Monodentate phosphoramidite ligands have been developed based on enantiopure 6,6-dimethylbiphenols with axial chirality. These chiral ligands are easy to prepare and flexible for modifications. The fine-tuning capability of these ligands plays a significant role in achieving high enantioselectivity in the asymmetric hydroformylation of allyl cyanide and the conjugate addition of diethylzinc to cycloalkenones. R ecently, chiral monodentate phosphorus ligands (phosphites, phosphoramidites, and phosphonites) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 28 publications
1
35
0
3
Order By: Relevance
“…These are often independent of catalyst concentration. As previously discussed, it is common for many mono-phosphorus ligands to form quite C. In the previous work by Ojima and co-workers [7], the enantiomerically pure form of ligand 2 gave poorer regioselectivity and no enantioselectivity in hydroformylation. It therefore seems very likely that this bulky ligand does not coordinate to rhodium under hydroformylation conditions, and that the higher branched selectivity observed for propene hydroformylation with ligand 2 relative to ligand 1 ( Table 1), is almost certainly due to the unmodified catalyst.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…These are often independent of catalyst concentration. As previously discussed, it is common for many mono-phosphorus ligands to form quite C. In the previous work by Ojima and co-workers [7], the enantiomerically pure form of ligand 2 gave poorer regioselectivity and no enantioselectivity in hydroformylation. It therefore seems very likely that this bulky ligand does not coordinate to rhodium under hydroformylation conditions, and that the higher branched selectivity observed for propene hydroformylation with ligand 2 relative to ligand 1 ( Table 1), is almost certainly due to the unmodified catalyst.…”
Section: Resultsmentioning
confidence: 97%
“…Ojima and co-workers [7] reported the use of enantiopure mono-dentate phosphoramidites in the enantioselective hydroformylation of allyl cyanide. Allyl cyanide does tend to give preference for the branched aldehyde [7,8] but the regioselectivity reported for ligand 1 is unusually high (B:L 96:4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When vinyl acetate was the substrate, very poor ees were obtained (Scheme 13) [49,50]. However, in 2004, Ojima and co-workers reported the use of the phosphoramidite ligand 55 (Scheme 13), related to monophosphite 54, in the Rh-catalyzed asymmetric hydroformylation of allyl cyanide and achieved excellent regioselectivities together with the highest enantiomeric excess (80%) ever reported for this reaction with a monodentate ligand [86]. These results, although still far from those obtained with bidentate ligands, clearly indicated that achieving high ees using monodentate ligands is possible.…”
Section: Monodentate Phosphorus-based Ligandsmentioning
confidence: 92%
“…Therefore, the presence of a single coordination isomer, in this case with ligand coordinated in an 86 B.F. Perandones et al…”
Section: 3-diphosphite Ligandsmentioning
confidence: 94%